Drought and root herbivory in understorey Parashorea Kurz (Dipterocarpaceae) seedlings in Borneo - Bebber, D; Brown, N; Speight, M (2002)
The influence of herbivory on dipterocarp seedling growth and survival in Bornean primary lowland forest understorey during and after the 1997-8 El Niño-Southern Oscillation was investigated. During the drought, a coleopteran (Scolytidae) root borer attacked dipterocarp seedlings, primarily of the genus Parashorea. Infestation was spatially heterogeneous on a large (c. 100 m) scale. Attack rate decreased with plant vigour within infested areas. Experiments showed that root damage was fatal under drought conditions, but not after rain. Defoliation and apical meristem removal did not increase mortality. The spatio-temporal heterogeneity of herbivore outbreaks and difficulties involved in experimenting with root herbivores limit the power of such short-term investigations. However, the study shows that herbivores can cause differential mortality between species, and can therefore influence dipterocarp regeneration dynamics. The effect of herbivory depends on the plant organ attacked and interactions with other stresses such as drought. El Niño-related droughts are increasing in frequency in South-East Asian rain forests, which may lead to increased numbers of herbivore outbreaks and greater seedling mortality due to these factors.